Long time gone [large type] - Donlea, Charlie (Thorndike Press, a part of Gale, a Cengage Company, 2024)
"On the first day of an elite two-year fellowship under the renowned Chief Medical Officer Dr. Livia Cutty, Sloan Hastings receives a research assignment in the emerging field of forensic genealogy. It's the exciting, rapidly evolving science behind the recent breaks in high-profile cold cases from the Golden State Killer to the Cameron Young murder, and Sloan enthusiastically begins her research by submitting her own DNA to an online genealogy site. Her goal is to better understand the treasure trove of genetic information contained on ancestry websites, but the results she receives are shocking. Raised by loving, supportive parents, Sloan has always known she was adopted. But her DNA profile suggests her true identity is that of Charlotte Margolis, aka "Baby Charlotte," who captured the nation's attention when she and her affluent parents mysteriously vanished in July 1995. Despite a large-scale investigation and months of broad media coverage, there were never any suspects in the family's disappearance and the case has been cold for decades. Racing to stay ahead of the media and true crime junkies ravenous to know what really happened to Baby Charlotte, Sloan's search for answers leads her to Cedar Creek, Nevada, a small town north of Lake Tahoe. There, the Margolis family's power and influence permeate every corner of the county, and while Sloan's birth relatives are initially welcoming, they're also mysterious and tight-lipped. Not everyone seems happy about Sloan's return, or the questions she's asking"--